Challenges for seismic velocity modelling of rafts and impacts for pre-salt depth estimations. Issue 1 (February 2023) - Camargo, Gisele Nery; González, María; Borges, Filipe; Maul, Alexandre; Mohriak, Webster U.
No abstract available